Sosialisasi Pemanfaatan Pakan Fermentasi Pada CV. Fadhilah Farm Untuk Meningkatkan Pengetahuan Sumber Daya Manusia Dan Mutu Pakan Ternak - Mustaqim, Mustaqim; Anita, Khairani; Yossie, Ulfa Nuzalifah; Findi, Septiani (Aceh Journal of Community Engagement (AJCE), 2024)
Livestock plays an important role in terms of providing animal protein, social and economic (source of income and/or savings for livestock farmers) in the farming system in Indonesia. Fermentation is the process of preserving feed by providing starters (microorganisms) which is carried out anaerobically. The mechanism for implementing this community service program is carried out with the stages of problem and needs analysis, offering cooperation with partners, implementing activities, and evaluating activities. In community service activities, the stages that will be carried out to increase knowledge and skills will be outlined. The results obtained are an increase in knowledge, skills and attitudes in livestock business owners and workers at CV. Fadhilah Farm will utilize agricultural waste as raw material for making fermented feed and how to make it.